Openness and economic growth in developing countries - Erich Gundlach (Kiel Institute of World Economics (IfW), 1996)
Openness appears to have a strong impact on economic growth especially in DCs, which typically exhibit a high share of physical capital in factor income and a low share of labor. In the neoclassical growth model with partial capital mobility, physical capital's share in factor income determines the difference in the predicted convergence rates for open and closed economies. With a 60 percent share as in developing countries, the convergence rates should differ by a factor of about 2.5. My regression results for a sample of open and closed DCs roughly confirm this hypothesis.
Keywords: O41; 330